Tibor Király (1920–2021) (Academic Journal of Internal Affairs, 2022)
On December 28, 2021, academician Tibor Király, an internationally renowned scientist, Széchenyi Prize awarded university professor, professor of criminal procedure law, and one of the most prestigious cultivators in the field of criminal sciences, has deceased. He obtained his legal qualification in Bratislava during the Second World War and his second degree in Budapest in 1948.
Keywords: obituary; professor; academician; criminal procedure